Occurrence, diversity and distribution of Trypanosoma infections in cattle around the Akagera National Park, Rwanda. - Richard Gashururu S; Ndichu Maingi; Samuel M Githigia; Methode N Gasana; Peter O Odhiambo; Dennis O Getange; Richard Habimana; Giuliano Cecchi; Weining Zhao; James Gashumba; Joel L Bargul; Daniel K Masiga (Public Library of Science (PLoS), 2021)
Background African Trypanosomiases threaten the life of both humans and animals. Trypanosomes are transmitted by tsetse and other biting flies. In Rwanda, the African Animal Trypanosomiasis (AAT) endemic area is mainly around the tsetse-infested Akagera National Park (NP). The study aimed to identify Trypanosoma species circulating in cattle, their genetic diversity and distribution around the Akagera NP. Methodology A cross-sectional study was carried out in four districts, where 1,037 cattle blood samples were collected. The presence of trypanosomes was determined by microscopy, immunological rapid test VerY Diag and PCR coupled with High-Resolution Melt (HRM) analysis. A parametric test (ANOVA) was used to compare the mean Packed cell Volume (PCV) and trypanosomes occurrence. The Cohen Kappa test was used to compare the level of agreement between the diagnostic methods. Findings The overall prevalence of trypanosome infections was 5.6%, 7.1% and 18.7% by thin smear, Buffy coat technique and PCR/HRM respectively. Microscopy showed a low sensitivity while a low specificity was shown by the rapid test (VerY Diag). Trypanosoma (T.) congolense was found at a prevalence of 10.7%, T. vivax 5.2%, T. brucei brucei 2% and T. evansi 0.7% by PCR/HRM. This is the first report of T.evansi in cattle in Rwanda. The non-pathogenic T. theileri was also detected. Lower trypanosome infections were observed in Ankole x Friesian breeds than indigenous Ankole. No human-infective T. brucei rhodesiense was detected. There was no significant difference between the mean PCV of infected and non-infected animals (p>0.162). Conclusions Our study sheds light on the species of animal infective trypanosomes around the Akagera NP, including both pathogenic and non-pathogenic trypanosomes. The PCV estimation is not always an indication of trypanosome infection and the mechanical transmission should not be overlooked. The study confirms that the area around the Akagera NP is affected by AAT, and should, therefore, be targeted by the control activities. AAT impact assessment on cattle production and information on the use of trypanocides are needed to help policymakers prioritise target areas and optimize intervention strategies. Ultimately, these studies will allow Rwanda to advance in the Progressive Control Pathway (PCP) to reduce or eliminate the burden of AAT.